Analisis Kekerabatan 50 Aksesi Kelapa Sawit (Elaeis guineensis Jacq.) Asal Kamerun Berdasarkan Marka Mikrosatelit - I Made Tasma; Ahmad Warsun; Dani Satyawan; Syafaruddin Syafaruddin; Budi Martono (Jurnal AgroBiogen, 2013)
Genetic diversity of theIndonesian oil palm collection remains low and collectionenrichness through exploration activities from the center oforigins is required. In 2009, 103 oil palm accessions fromCameroon were collected at the National Oil Palm GeneticResources Collection located at the District of Sijunjung,West Sumatera. The objectives of the present study were toanalayze the 50 Cameroon-originated oil palm accessions inorder to: (1) determine polymorphism levels of the SSRmarkers used; (2) understand diversity levels of the oil palmaccessions tested; and (3) analyze accessions potentiallyused for germ plasm collection. Fifty oil palm accessionswere used in this study. DNA was isolated from leaves of theselected individual plants representing each of theaccessions. DNA was analyzed with 12 SSR markers. Adendrogram was constructed using the UPGMA throughNumerical Taxonomy and Multivariate System programversion 2.1-pc. Results showed that SSR markers useddemonstrated the average number of alleles per locus of 3.6(2-6). The polymorphism level was 0.53 (0.21-0.73). Thephylogenetic analysis resulted nine clusters with geneticdiversity between two accessions ranged from 4-82%. Tenaccessions (20%) showed low genetic diversity (<10%) butthe accessions demonstrated high diversity in floweringtime. Eleven accessions showed medium diversity level (27-42%). Five accessions demonstrated high genetic diversitylevel (45-82%). A confirmation study using more SSRmarkers is recommended. This study finding may be usefulin planning the oil palm germ plasm collection activities.